Energy consumption and carbon dioxide emission considerations in the urban planning process in Malaysia - Wee, Kean Fong; Matsumoto, Hiroshi; Ho, Chin Siong; Yu, Fat Lun (2008)
It is now recognized that this planet and the mankind are under serious threat of global warming, thus immediate actions are required to fight against it. Among of the most important measures are to reduce energy consumptions and carbon dioxide emissions. The objectives of this study are thus to examine the current situation of energy conservation and carbon dioxide emission in Malaysia, and their considerations in the spatial planning process. While many countries have recognized the importance of the role of urban planning in energy conservation and reduction of carbon dioxide emissions, spatial planning framework in Malaysia is still lacking in this aspect. Although there are some spatial planning policies indirectly favor energy conservation, there is still no measure that directly emphasizes on promoting energy conservation and capping carbon dioxide emissions. Energy and carbon dioxide issues should thus be taken as one of the core parts in the urban planning process. While achieving the desired socio-economic developments, it is necessary to create a low energy consumptions and low carbon sustainable society.